Age-related differences in characteristics of anaphylaxis in Chinese children from infancy to adolescence - Nannan Jiang, MD (Elsevier, 2021)
Background: Little is known about anaphylaxis in Chinese children. This study aimed to determine the age-specific patterns of anaphylaxis in Chinese children. Methods: We conducted a retrospective study of anaphylaxis cases attending an allergy department in a tertiary children's hospital. Results: A total of 279 anaphylactic reactions in 177 patients were analyzed. Overall, 57.6% (102/177) of first anaphylaxis events occurred in infants (0–2 ys). Foods were the most common culprits (88.5%), followed by food + exercise/exercise (4.7%), and drugs (4.3%). The main food allergens were cow's milk (32.9%), egg (21.4%), and wheat (20.7%) in infants, compared with fruits/vegetables at 35.9% in preschool-age children (3–6 ys) and 31.6% in school-age children (7–12 ys). The most commonly implicated drug triggers were vaccines (n = 5, comprising DTaP n = 2, group A + C meningococcal polysaccharide vaccine n = 1, Sabin vaccine n = 1, and not specified n = 1). Among the 5 vaccine-induced anaphylaxis patients, 4 had severe cow's milk allergy. The clinical manifestations were mainly mucocutaneous (86.0%), followed by respiratory (68.8%), gastrointestinal (23.7%), neurological (10.4%), and cardiovascular (0.7%). Compared with patients of other ages, infants had higher rates of hives (0-2ys 77.4%, 3-6ys 50%,7-12ys 57.9%, 13-17ys 38.9%, p = 0.016) and vomiting (0-2ys 20.7%, 3-6ys 1.6%,7-12ys 8.8%, p < 0.001), while wheezing was more frequent in school-age children (0-2ys 21.4%, 3-6ys 25%, 7-12ys 38.6%, 13-17ys 5.6%, p = 0.017) and abdominal pain was more common in adolescents (0-2ys 2.1%,3-6ys 15.6%, 7-12ys 14.0%, 13-17ys 72.3%, p < 0.001). Regarding treatment, 9.3% of anaphylaxis events and 24.1% of life-threatening reactions were treated with epinephrine. Conclusions: We observed age-related clinical patterns of anaphylaxis in this study, with hives and vomiting most commonly reported in infants and cardiovascular symptoms rarely reported in children. Wheat was the third most culprit food allergen after egg and milk in infancy. Education regarding more aggressive use of epinephrine in the emergency setting is clearly needed. Recognition of age-related symptoms in anaphylaxis can aid physicians in prompt diagnosis and acute management.